Infrared thermography of in situ natural freezing and mechanism of winter‐thermonasty in Rhododendron maximum. Issue 2 (7th March 2023) - Arora, Rajeev; Wisniewski, Michael; Tuong, Tan; Livingston, David
Abstract: Evergreen leaves of Rhododendron species inhabiting temperate/montane climates are typically exposed to both high radiation and freezing temperatures during winter when photosynthetic biochemistry is severely inhibited. Cold‐induced "thermonasty, " that is, lamina rolling and petiole curling, can reduce the amount of leaf area exposed to solar radiation and has been associated with photoprotection in overwintering rhododendrons. The present study was conducted on natural, mature plantings of a cold‐hardy and large‐leaved thermonastic North American species ( Rhododendron maximum ) during winter freezes. Infrared thermography was used to determine initial sites of ice formation, patterns of ice propagation, and dynamics of the freezing process in leaves to understand the temporal and mechanistic relationship between freezing and thermonasty. Results indicated that ice formation in whole plants is initiated in the stem, predominantly in the upper portions, and propagates in both directions from the original site. Ice formation in leaves initially occurred in the vascular tissue of the midrib and then propagated into other portions of the vascular system/venation. Ice was never observed to initiate or propagate into palisade, spongy mesophyll, or epidermal tissues. These observations, together with the leaf‐ and petiole‐histology, and a simulation of the rolling effect of dehydrated leaves using a cellulose‐based, paper‐bilayer system, suggest that thermonasty occurs due to anisotropic contraction of cell wall cellulose fibers of adaxial versus abaxial surface as the cells lose water to ice present in vascular tissues.